The “Person of Rubbish” And the Modern State: Temptation Mechanisms - Ковтун, Наталья (Literatūra, 2016)
The article is devoted to the problem of existence of the person of post-industrial society as he is presented in anti-utopian texts of the 1990s. The emphasis on the 1990s isn’t casual, the era sums up the results at this time through and by literature, the main tendencies and characteristic types are highlighted. In epoch-making times, the person of crowd also declares himself. By differentiation of concepts of the mass person and the person of crowd, we construct the image of “the person of rubbish”, which survived on shatters of former utopias and mythologemas. The person of rubbish, in our opinion, is a transcription of the ancient Ham, left a shadow of heroic eras. The story “Laz” (Manhole) of V. Makanin describes the strategies of a survival of intellectual singles, crowds and inhabitants in post-apocalyptic time, their relationship with the state. The text testifies that a victory of the Unitary State (for which in a classical utopia prepared through Great operation, fear, denunciations) proved to be a Pyrrhic victory. So far, the power gives the last guards on sacrifice, and the intellectuals go to races, the crowd commits excesses, sees in the State not the Benefactor and Leader but the unworthy, disgusting competitor in fight for a survival, still armed and dangerous. The state, carrying out social surgery on removal of the top, intellectual levels of public consciousness, kindling primitive passions, appeared in private with criminals who are tolerant to former mechanisms of temptation. The destruction of soul, the imagination will (there was the aim of the Great operation) turn back the rudeness of revelry. The infantile, dexterous, indifferent and aggressive “person of rubbish” ceased to bargain and argue with the Leviathan, forgot to read and dream, what led to a stop of history, life disappearance.
Keywords: anti-utopia; Makanin; Manhole; crowd; person of rubbish; Ham